MOTION COORDINATION OF MULTI-AGENT ROBOTICS SYSTEMS - Kyzyrkanov А.; Atanov С.; Tursynova Н.; Aljawarneh Ш. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2022)
For multi-agent robotic systems, motion with a certain geometric pattern, has many advantages: system costs are reduced, efficiency and consistency are improved, and structure flexibility is increased. This paper considers the movement of multi-agent robotic systems maintaining a certain geometric structure. A motion coordination algorithm based on a behavior is described. To maintain the geometric form, the leader-follower method was used, and in order that the state of the system did not depend on the state of individual robots, it was proposed to define a virtual leader. Also in this work, the motion of a multi-agent robotic system with four autonomous robots was simulated. The results of the experimental study of the motion of the system by using the algorithm described in this paper are provided.